Current situation of research on family life in Malaysia - Wan Ahmad, Wan Ibrahim (American-Eurasian Network for Scientific Information (AENSI Publisher), 2013)
The main theme of the special issue will be “current situation of research on family life in Malaysia”, addressing some of the key priorities on family life and its importance in human society in Malaysia. The nature of family in Malaysia, as in other parts of the world, is changing over time.All these papers represent the continuous research interests by the members of our colleagues.While research interests are divers, this volume will only cover themes related to research on family life and its importance.